Investigating the mediating role of the meaning of life in the relationship between perceptions of parenting styles and the academic life of second-year secondary school students in Zanjan city. - Ataaei Zanjaninejad, Zahra; Hejazi, Masoud; Sobhi, Afsaneh; Ahmadi, Mohammad Saaeid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: The meaning of life in a person can affect other aspects of his life. The academic vitality of people is among them; Therefore, this research was conducted with the aim of investigating the relationship between the perception of parenting styles and academic life with the mediating role of the meaning of life in the second secondary school students of Zanjan city. Methods: This is descriptive correlational research. The statistical population was 20,866 students of the second secondary school in Zanjan city in the academic year 2019-20. According to Morgan’s table, 392 people were selected, but to increase the credibility of the findings, 400 people were selected and distributed by stratified random method. To collect data, the standard questionnaires of Alabama parenting (1991), Hossein Chari and Dehghanizadeh’s academic vitality (2013) and the meaning of life were used by Sticker et al. (2006). The data was analyzed using SPSS.24 statistical software and AMOS statistical software was used for modeling structural equations. Results: The results showed that; There is a significant relationship between the perception of parenting styles and academic vitality (p<0.01) and also, there is a significant relationship between the perception of parenting styles and the meaning of life (p<0.01). The meaning of life plays a mediating role in the relationship between parenting styles and academic vitality (p<0.01). Conclusion: It can be concluded that in order to create academic vitality in students, perceptions of parenting styles play a decisive role and the meaning of life can lead to academic vitality in children.